2017
DOI: 10.3991/ijet.v12i02.6681
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-assisted Language Learning Using WeChat Instant Messaging

Abstract: Abstract-China has a long-standing problem in second-language education, that is, the lack of communicative learning opportunities. This study attempts to solve the problem by introducing mobile-assisted language learning with WeChat instant messaging. WeChat is one of the most popular instant messaging applications in China. It offers five advantages for education: multifunctionality, individuality, accessibility, interactivity, and affordability. 50 students participated in a one-semester program. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 4 publications
3
30
0
Order By: Relevance
“…Studies on popular instant messaging applications like WeChat have shown a positive result in improving L2 speaking skills in China [10]. The present study not only studies the impact of the platform on L2 speaking, but also studies perceptions of the participants on speaking assessment criteria.…”
Section: Learning Through Whatsappmentioning
confidence: 91%
“…Studies on popular instant messaging applications like WeChat have shown a positive result in improving L2 speaking skills in China [10]. The present study not only studies the impact of the platform on L2 speaking, but also studies perceptions of the participants on speaking assessment criteria.…”
Section: Learning Through Whatsappmentioning
confidence: 91%
“…The game element anonymity, which allows a user to mask their identity or assume the identity of an avatar, fulfils this purpose. Language learners have found it easier to chat in a target language using a messaging system or find that using such a system increases their confidence [163,164]. Therefore, it is understandable that using a massively multiplayer online game with chat functionality can facilitate a similar type of environment.…”
Section: Anonymity and Anxietymentioning
confidence: 99%
“…• MALL Tools: For foreign language learning programs, MALL (Mobile Assisted Language Learning) tools, including messaging services, could be used. Messaging apps such as WeChat in the EFL (English as Foreign Language) context could enhance students' English proficiency and motivation [17]. • LFO Panel: In addition to the existing tools, we developed the LFO (Learn From Others) Panel, a tool for experiential learning, known to be a rather complex form of active [18], [19].…”
Section: Fig 2 Learning Environment Aris Systemmentioning
confidence: 99%